2016
DOI: 10.1111/bju.13037
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and beliefs towards management of men with locally advanced prostate cancer following radical prostatectomy: an Australian survey of urologists

Abstract: ObjectiveTo investigate Australian urologists' knowledge, attitudes and beliefs, and the association of these with treatment preferences relating to guideline-recommended adjuvant radiotherapy for men with adverse pathologic features following radical prostatectomy. Subjects and methodsA nationwide mailed and web-based survey of Australian urologist members of the Urological Society of Australia and New Zealand (USANZ). Results157 surveys were included in the analysis (45% response rate). Just over half of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Unintentional non‐adherence arises from lack of knowledge regarding the existence and content of clinical guidelines . Even when clinicians use guidelines in regular practice, the specific details of the recommendations within may not be well known , and many do not agree that recommendations are based on valid interpretations of the evidence . Our results would appear to show that unintentional non‐adherence has been a major contributor to guideline‐discordant imaging in our region.…”
Section: Discussionmentioning
confidence: 79%
“…Unintentional non‐adherence arises from lack of knowledge regarding the existence and content of clinical guidelines . Even when clinicians use guidelines in regular practice, the specific details of the recommendations within may not be well known , and many do not agree that recommendations are based on valid interpretations of the evidence . Our results would appear to show that unintentional non‐adherence has been a major contributor to guideline‐discordant imaging in our region.…”
Section: Discussionmentioning
confidence: 79%
“…A lack of consensus guidelines on management serves to remind us of the gaps in the literature to provide high-level evidence on the best pathways to follow (22). This study demonstrates that urinary leakage following RALP considerably improves in the short-term with the aid of pelvic floor physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Full details of survey development have been previously published. 11 Briefly, the survey comprised six sections relating to: (i) clinical equipoise; (ii) use of, and attitudes and beliefs towards, clinical guidelines in practice; (iii) innovation and current clinical practice; (iv) barriers to adherence to a clinical practice recommendation; (iv) perceptions of organisational readiness for change; and (vi) demographic information. The survey predominantly used a 5-point Likert scale ('strongly disagree' to 'strongly agree') coded as consecutive integers for analysis (with an additional 'don't know' option coded as missing).…”
Section: Survey Domainsmentioning
confidence: 99%
“…In 2012, two years after the release of the Australian Cancer Network Clinical Practice Guidelines for the Management of Locally Advanced and Metastatic Prostate Cancer, 6 we conducted a nationwide survey to investigate Australian urologists' knowledge, attitudes and beliefs, and the association of these with treatment preferences relating to guideline-recommended adjuvant radiotherapy for men with adverse pathologic features following radical prostatectomy. 11 The survey provided baseline data to inform the development of the 'Clinician-Led Improvement in Cancer Care (CLICC)' implementation trial. 12 Results from the 2012 survey indicated that urologists varied in their attitudes and beliefs regarding adjuvant radiotherapy after radical prostatectomy for men with adverse pathologic features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation